Pengaruh Kemampuan dan Motivasi Guru terhadap Prestasi Belajar Siswa Kelas XI SMKN-2 Palangka Raya - Sumarnie (JURNAL PENDIDIKAN, 2020)
The research aims to described the significance of the effect of : 1) theteacher's ability on the student achievement, 2) the teachers’ motivation toteach on student achievement, 3) the teachers’ ability and motivation toteach on student achievement in class XI Sekolah Menengah KejuruanNegeri (SMKN-2) Palangkaraya. The method used the survey methodassociative exsploration level with the relationship of causal variables andtypes of quantitative data. The population as sampel of research of 35students by taking all members of the "population", as a sample (totalsample). Based on the results of data analysis, it can be concluded that theability and motivation of teachers significantly influences the learningachievement of Grade of XI students of Sekolah Menengah Kejuruan Negeri(SMKN) 2 Palangkaraya of 82.40% positively and the regression equationof Y = 2.94 + 0.60X1 +0.68X2 . While 27.60% is influenced by other thingssuch as the social background of students, family conditions, abilities andattitudes the teacher has a very large share in influencing studentachievement.